2018
DOI: 10.1002/lary.26877
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of type I thyroplasty after endoscopic cordectomy for early‐stage glottic cancer: Literature review

Abstract: Optimizing voice after EC remains a clinical challenge. Our review suggests that thyroplasty is one potentially beneficial option in appropriately selected patients. More controlled studies are needed to assess efficacy of thyroplasty in this context. Laryngoscope, 128:690-696, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This finding is in accordance with the current literature, which has found thyroplasty to be a safe and effective method for closing glottic gaps after extended or total cordectomy. [26][27][28] This study has several limitations. It is difficult to generalize these experiences to other institutions, given the variability in patient populations and surgeon experience.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding is in accordance with the current literature, which has found thyroplasty to be a safe and effective method for closing glottic gaps after extended or total cordectomy. [26][27][28] This study has several limitations. It is difficult to generalize these experiences to other institutions, given the variability in patient populations and surgeon experience.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is in accordance with the current literature, which has found thyroplasty to be a safe and effective method for closing glottic gaps after extended or total cordectomy. 26 -28…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Bertelsen et al found that medialization thyroplasty is a useful tool in enhancing voice after cordectomy [ 20 ]. Villaret and colleagues reported on voice outcomes following intra-operative autologous fat injections into the neocord after type III laser cordectomy.…”
Section: Discussionmentioning
confidence: 99%
“…When TLM is used to treat early glottic cancers, the size of the glottic gap is influenced by the amount of tissue resected for oncologic control. The degree of post-operative dysphonia correlates directly with the size of the glottic gap [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A novel endoscopic AA with IL was developed as a rapid, minimally invasive solution for UVFP (49). There were adverse events associated with thyroplasty, including hematoma, infection, and implant extrusion (50).…”
Section: Type I Thyroplasty and Aamentioning
confidence: 99%